Relative survival after diagnosis with a primary brain or other central nervous system tumor in the National Program of Cancer Registries, 2004 to 2014. Issue 3 (16th December 2019) - Ostrom, Quinn T; Truitt, Gabrielle; Gittleman, Haley; Brat, Daniel J; Kruchko, Carol; Wilson, Reda; Barnholtz-Sloan, Jill S
Abstract: Background: The majority of reported cancer survival statistics in the United States are generated using the National Cancer Institute's publicly available Surveillance, Epidemiology, and End Results (SEER) data, which prior to 2019 represented 28% of the US population (now 37%). In the case of rare cancers or special subpopulations, data sets based on a larger portion of the US population may contribute new insights into these low-incidence cancers. The purpose of this study is to characterize the histology-specific survival patterns for all primary malignant and nonmalignant primary brain tumors in the United States using the Centers for Disease Control and Prevention's National Program of Cancer Registries (NPCR). Methods: Survival data were obtained from the NPCR (includes data from 39 state cancer registries, representing 81% of the US population). Relative survival rates (RS) with 95% CI were generated using SEER*Stat 8.3.5 from 2004 to 2014 by behavior, histology, sex, race/ethnicity, and age at diagnosis. Results: Overall, there were 488 314 cases from 2004 to 2014. Overall 5-year RS was 69.8% (95% CI = 69.6%-69.9%). Five-year RS was 35.9% (95% CI = 35.6%-36.1%) for malignant and 90.2% (95% CI = 90.1%-90.4%) for nonmalignant tumors. Pilocytic astrocytoma had the longest 5-year RS (94.2%, 95% CI = 93.6%-94.6%) of all glioma subtypes, whereas glioblastoma had the shortest 5-year RS (6.1%, 95% CI = 6.0%-6.3%). Nonmalignant nerve sheath tumors had the longest 5-year RS (99.3%, 95% CI = 99.1%-99.4%). Younger age and female sex were associated with increased survival for many histologies. Conclusions: Survival after diagnosis with primary brain tumor varies by behavior, histology, and age. Using such a database that includes more than 80% of the US population may represent national survival patterns.